Lamotrigine and retigabine increase motor threshold in transcranial magnetic stimulation at the dose required to produce an antiepileptic effect against maximal electroshock-induced seizure in rats. (6th February 2022) - Hotta, Natsu; Miyamoto, Maki; Suzuki, Kazunori
Highlights: Lamotrigine and retigabine increase the motor threshold in rats using TMS. Lamotrigine and retigabine inhibit maximal electroshock-induced seizures in rats. Effective doses in the TMS study are equivalent to those for antiepileptic effects. TMS study may be a useful translational approach for predicting antiepileptic effects. Abstract: Transcranial magnetic stimulation (TMS) is a neurophysiological technique that enables noninvasive evaluation of neuronal excitability in the brain. In the past, a large number of antiepileptic drugs were shown to increase the motor threshold (MT) in clinical TMS studies, suggesting the inhibition of excessive neuronal excitability. To facilitate drug development, the confirmation of similar changes in neurophysiological biomarkers in both preclinical and clinical studies is crucial; however, until now, there have been no data showing the drug efficacies on neuronal excitabilities as measured using TMS in rodents. In this study, we found that the antiepileptic drugs, lamotrigine (10 mg/kg) and retigabine (5 mg/kg), significantly increased the MT in rats using TMS, which is similar to clinical study findings. In addition, we demonstrated that these drugs could inhibit maximal electroshock (MES)-induced seizures in rats when given at the same dose required to be effective in the TMS experiment. These findings suggest that the effects of antiepileptic drugs in our rat TMS system have a similar sensitivity to that of the antiepileptic effects in rats with MES-induced seizures. The measurement of MT in a TMS study may be a noninvasive translational approach for predicting antiepileptic efficacy in drug development.